Social Media as Communication Strategy for Susi Pudjiastuti to Build Maritime Security Awareness in Indonesia - Andyna Sary (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2019)
Indonesia faces a number of serious and urgent challenges in the area of maritime security; including, Illegal, Unreported and Unregulated Fishing, Maritime Plastic Pollution, and serious Transnational Organized Crimes such as human trafficking and forced labor. One figure in Indonesian politics stands out for her efforts to eradicate these crimes, Susi Pudjiastuti, the Indonesian Minister for Marine Affairs and Fisheries since 2014. Minister Pudjiastuti has been remarkable both for her enforcement of previously-unutilized laws to seize and destroy illegal vessels, and her use of social media to promote awareness and action within the general public. The article takes a mixed-methodology approach to measure and analyze Pudjiastuti’s strategic use of social media as a key weapon in her fight against crime in the maritime sector. This research used Governmental Communication Theory by Canel & Sanders (2013), New Media by Marshall McLuhan, and also Humanistic Leadership Model by Robert Blake and Jane Mouton. Through quantitative and qualitative analysis of Pujiastuti’s Instagram and Twitter posts, the thesis reveals a very high level of influence, awareness-raising and engagement with her message. The findings are that her innovative used of social media indicates a new paradigm of direct, transparent political engagement with the public that sets a high benchmark for other Indonesian leaders and politicians.